Peningkatan Fungsi Kognitif Lansia melalui Crossword Puzzle Therapy (CPT) - Safitri, Dwinita Aprilia; M.Noer, Rachmawaty; Wulandari, Yulianti (Journal of Hospital Administration and Management (JHAM), 2025)
The aging process experienced by the elderly causes problems in physical, mental, and behavioral development. The physical abilities of the elderly decline with age, causing problems with cognitive decline in the elderly. One intervention that can be done in the elderly to stop cognitive decline is Crossword Puzzle Therapy (CPT) which can improve cognitive abilities, enhance memory, and improve understanding. To determine the effect of Crossword Puzzle Therapy (CPT) on the cognitive function of the elderly in the Tanjung Unggat Community Health Center working area in Tanjungpinang City. The research method used was a quasi experimental design with a One Groups Pretest-Posttest Design approach. The sample in this study consisted of 33 elderly patients treated at the Tanjung Unggat Community Health Center in Tanjungpinang City, and the sampling technique used was purposive sampling. This study used a normality test with a sig. value > 0.005 and continued with a non-parametric test, namely the Wilcoxon test. The results of the study showed a P value of 0.000, which means that the significance value is < 0.05, so that Crossword Puzzle Therapy (CPT) has a significant effect on cognitive function, namely H0 is rejected and Ha is accepted. There is an effect of Crossword Puzzle Therapy (CPT) on cognitive function in the working area of the Tanjungunggat Community Health Center in Tanjungpinang City with a P value of 0.000. It is hoped that community health centers can implement Crossword Puzzle Therapy (CPT) to improve the health quality of the elderly, especially in handling their cognitive function.